Long Non-coding RNAs Rian and Miat Mediate Myofibroblast Formation in Kidney Fibrosis - Bijkerk, Roel; Au, Yu Wah; Stam, Wendy; Duijs, Jacques M. G. J.; Koudijs, Angela; Lievers, Ellen; Rabelink, Ton J.; van Zonneveld, Anton Jan (Frontiers in Pharmacology, 2019)
There is an increasing prevalence of chronic kidney disease (CKD), which associates with the development of interstitial fibrosis. Pericytes (perivascular fibroblasts) provide a major source of α-SMA-positive myofibroblasts that are responsible for the excessive deposition of extracellular matrix. In order to identify pericyte lncRNAs that could serve as a target to decrease myofibroblast formation and counteract the progression of kidney fibrosis we employed two models of experimental kidney injury, one focused on kidney fibrosis (unilateral ureteral obstruction; UUO), and one focused on acute kidney injury that yields kidney fibrosis in the longer term (unilateral ischemia-reperfusion injury; IRI). This was performed in FoxD1-GC;tdTomato stromal cell reporter mice that allowed pericyte fate tracing. Tomato red-positive FoxD1-derivative cells of control and injured kidneys were FACS-sorted and used for lncRNA and mRNA profiling yielding a distinctive transcriptional signature of pericytes and myofibroblasts with 244 and 586 differentially expressed lncRNAs (>2-fold, p<0.05), in the UUO and IRI models respectively. Next, we selected two differentially expressed and conserved lncRNAs, Rian (RNA imprinted and accumulated in nucleus) and Miat (Myocardial infarction associated transcript), and explored their potential regulatory role in myofibroblast formation through knockdown of their function with gapmers. While Miat was upregulated in myofibroblasts of UUO and IRI in mice, gapmer silencing of Miat attenuated myofibroblast formation as evidenced by decreased expression of α-SMA, col1α1, SMAD2 and SMAD3, as well as decreased α-SMA and pro-collagen-1α1 protein levels. In contrast, silencing Rian, which was found to be downregulated in kidney myofibroblast after IRI and UUO, resulted in increased myofibroblast formation. In addition, we found microRNAs that were previously linked to Miat (miR-150) and Rian (14q32 miRNA cluster), to be dysregulated in the FoxD1-derivative cells, suggesting a possible interaction between miRNAs and these lncRNAs in myofibroblast formation. Taken together, lncRNAs play a regulatory role in myofibroblast formation, possibly through interacting with miRNA regulation, implicating that understanding their biology and their modulation may have the potential to counteract the development of renal fibrosis.